Desertification Due to Ecological Changes in The Vegetation of Indian desert - Saxena, S K (Annals of Arid Zone, 2016)
Over-exploitation of the natural vegetation by way of overgrazing and removal of tree species for fuel and for other purposes and cultivation of marginal lands like sand dunes etc. lead to a series of ecological changes in the desert area of western Rajasthan due to which the whole tract becomes susceptible to erosion hazards and this finally ieads to desertification.